Ayam Gepuk Pak Gembus Web-Based Ordering Application Design With Codeigniter Framework - Yusuf Kurnia; Refin . (bit-Tech, 2019)
The difficulty of finding the desired food and to buy it also one of the problems that almost everyone faces. This problem occurs because the desired item is only sold in a certain place or rare. We need a way to solve the problem. One of them is e-commerce, which mostly uses the internet network. By making a ordering program, customers can see a list of foods sold and can order food from far away and the transaction process becomes safer and easier. Therefore the author conducted a research in a place / business called Ayam Gepuk Pak Gembus Dasana Indah Branch, and the author found several problems in the place like a narrow place to eat, so most people ordered to take home, the storage of data is still manual (storing it in paper) and the owner want to expand their business. So, the author decided to make a booking application for Ayam Gepuk Pak Gembus Dasana Indah Branch to make it easier for customers to order food, and also make the admin page so that the owner can monitor the income from his business, stock items, and view reports. At least the author made the ordering application using the CodeIgniter framework. MVC (Model-View-Controller) CodeIgniter framework that makes coding is divided into three, namely Controller, Model, and Views so that the coding is easy to read by new programmers in the future and there are already codes so programmers don't bother to look for codes.